The Effectiveness of Conservation Athletic Games for Non-Formal Education Learning Primary School Age (Edukasi, 2022)
Athletics is one of the elements of physical education as well as a component of overall education that prioritizes physical activity. This study aims to analyze the effectiveness of conservation athletic game products for elementary students. This research is done using a research and development approach. The development model used is the ADDIE model which includes analysis, design, development, implementation, and evaluation. The development of conservation athletic games includes: ) Lompat galah; 2) Roket; 3) Sunda manda; 4) Gapar; 5) Gayap; 6) Lompat tali; 7) Lari; 8) Zona rotasi; 9) Balap karung; 10) Lempar sasaran; 11) Gelindingan ban; 12) Estafet. The small-scale trial was given to 17 students at SDN 2 Honggosoco. A large-scale trial was conducted on 170 elementary school students in Kudus Regency. The results of this study stated that the results of physical education teachers showed the category of "Excellent" with a percentage of "100%". The results of the small-scale trial showed the category of "Excellent" with a percentage of "100%". The results of large-scale trials showed an "Excellent" category with a percentage of "98.50%". Conclusions indicate that athletic conservation is very effective for the learning of physical education of athletic materials in primary schools.